2008
DOI: 10.1080/00029890.2008.11920555
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Orbits for Billiards on an Equilateral Triangle

Abstract: Using elementary methods, we find, classify and count the classes of periodic orbits of a given period on an equilateral triangle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Here, we examine triangular optical billiards with sharp corners as open optical systems. It has been shown that the properties of trajectories in generic triangular billiards display a rich behavior depending crucially on the realized geometry [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we examine triangular optical billiards with sharp corners as open optical systems. It has been shown that the properties of trajectories in generic triangular billiards display a rich behavior depending crucially on the realized geometry [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…If you happen to be conversing with a mathematician, however, the term may instead bring to mind the wellknown dynamical system involving the motion of a particle within a closed domain. The billiard dynamical system has a great deal of intrinsic beauty (e.g., see Figure 1), is a source of mathematical connections (e.g., to number theory [1] and Cantor sets [6]), and has applications to phenomena like the classical motion of gas particles in a closed container [12], optics, and quantum chaos [5]. Even non-mathematicians may be interested in the mathematical version of billiards when they learn that Lewis Carroll investigated billiard trajectories within certain polyhedra [14].…”
Section: Introductionmentioning
confidence: 99%
“…An equilateral triangle billiard is also well-studied in both its classical and quantum incarnations [49][50][51][52][53][54]. The eigenspectrum for a quantum particle of mass µ trapped in an equilateral triangular box of side length L was obtained in [49,53,54].…”
Section: The Equilateral Triangle Billiardmentioning
confidence: 99%